Lung cancer screening: does pulmonary nodule detection affect a range of smoking behaviours? - Clark, Marcia E.; Young, Ben; Bedford, Laura E.; Robertson, John F.R.; das Nair, Roshan; Vedhara, Kavita; Sullivan, Francis; Mair, Frances S.; Schembri, Stuart; Littleford, Roberta; Kendrick, Denise (Oxford University Press, 2018)
Background Lung cancer screening can reduce lung cancer mortality by 20%. Screen-detected abnormalities may provide teachable moments for smoking cessation. This study assesses impact of pulmonary nodule detection on smoking behaviours within the first UK trial of a novel auto-antibody test, followed by chest x-ray and serial CT scanning for early detection of lung cancer (Early Cancer Detection Test-Lung Cancer Scotland Study). Methods Test-positive participants completed questionnaires on smoking behaviours at baseline, 1, 3 and 6 months. Logistic regression compared outcomes between nodule (n=95) and normal CT groups (n=174) at 3 and 6 months follow-up. Results No significant differences were found between the nodule and normal CT groups for any smoking behaviours and odds ratios comparing the nodule and normal CT groups did not vary significantly between 3 and 6 months. There was some evidence the nodule group were more likely to report significant others wanted them to stop smoking than the normal CT group (OR across 3 and 6 month time points: 3.04, 95%CI 0.95, 9.73; p=0.06). Conclusion Pulmonary nodule detection during lung cancer screening has little impact on smoking behaviours. Further work should explore whether lung cancer screening can impact on perceived social pressure and promote smoking cessation.